Advertising, Consumption and Economic Growth: An Empirical Investigation - Günther Rehme; Sara-Frederike Weisser (Technische Universität Darmstadt, Department of Law and Economics, 2007)
It is sometimes argued that more advertising raises consumption which in turn stimulates output and so economic growth. We test this hypothe- sis using annual German data expressed in terms of GDP for the period 1950-2000. We find that advertising does not Granger-cause growth but Granger-causes consumption. Consumption, in turn, Granger-causes GDP growth. The data imply that the immediate impact of more advertising on consumption is positive. However, the long-run effect is negative. Further- more, the immediate impact of higher consumption on growth is negative. But the long-run effect is positive. These results raise interesting questions for standard theory, political debates and advertising practioners.
Keywords: O4; M3; E2; 330; Advertising; Consumption; Economic Growth; Werbung; Gesamtwirtschaftlicher Konsum; Wirtschaftswachstum; Deutschland